Os saberes e as práticas docentes do professor tutor no ensino superior na modalidade a distância - Palermo, Roberta Rossi Oliveira (2018)
This research focuses on the context of the tutor teachers’ professional socializationand the respective implication concerning their knowledge and practices in Distance Education (DE) in Higher Education. It aims to gather elements that could explicit the characteristics of the tutor teacher’s work and under which conditions it happens. It is a bibliographic, documentary and field research, theoretically supported by authors related to the area of Sociology of Education, especially regarding the relations established among teaching work and professional identity: a) to identify the tutor teacher’s knowledge, Tardif and Raymond (2000), Borges (2001), Pimenta (2012), Gauthier (2013), Nóvoa (1999) and Perrenoud (2001); b) to elucidate the concept ofpoliteachingin distance education, Mill (2014); c) to identify the tutor teacher’s thinking and the professional background knowledge for the practice of the teaching work, Shulman (2005); d) to understand the teaching professional development, Marcelo Garcia (2009); e) to analyze the teaching professional insertion, Vaillant (2009); e) to understand the elements that characterize the teaching work, Tardif and Lessard (2009); f) to discuss the socialization and the teaching professional identity, Berger &Luckmann (2014) and Claude Dubar (1997) – other authors’ specific reference; g) to advance the concept of technology, Marcuse (1999); and h) to characterize pedagogical and institutional models, Marin (1990). The intention with the bibliographic research is to identify and characterize the studies related to this theme, as well as investigate the perspectives of analysis in the selected works, elucidating how the tutor teachers’ knowledge and professional performance in distance education in higher education are defined. The documentary research was accomplished by means of survey of specific legislation about distance education in higher education context in Brazil and documents from 02 Brazilian Higher Education institutions that, after mapping the higher education institutions that offer the undergraduate major in Education in distance education and that twice received the highest score at ENADE evaluation (National Exam of Evaluation of Students’ Performance) between 2005 and 2011, agreed to the solicitation of authorization for the survey. Finally, the field research included: a) contacts with those 02 selected institutions, 01 Coordinatorof the Undergraduate Major and 18 tutor teachers, that accepted to participate in the survey; b) creation and testing of instruments to data collection (Questionnaire, Interview Guidelines and Guidelines for the Analysis of Documents). Data collected were organized in tables, figures and charts, with the support of the SPHINX iQ2software, answering to the research questions: What do different scientific contributions express about the tutor teacher’s knowledge and work? What are the directions of the legislation regarding the distance education in Brazil, and especially concerning the tutor teacher? What do the documents from the surveyed institutions express about the definition and organization of the tutor teacher’s work, in distance education? Who are the tutor teachers and under which conditions do they work? Which teaching knowledge do the surveyed tutor teachers have and how is their work/performance characterized? The results obtained partially confirmed the hypothesis investigated, revealing that: a) the examined academic productions mainly focused on the analysis of the DE tutor teacher’s workversusthe teacher’s work in face-to-face instruction andon the precarization of the tutor teacher’s work, recognized as a tutor and not as a teacher; b) the Brazilian legislation has been contradictory regarding the tutor teacher’s space in DE, maintaining the teaching hierarchization in distance education; c) the investigated higher education institutions, though being public and federal and having adopted the UAB model (Open University of Brazil), present distinct forms of course development and tutor teacher’s work; d) the tutor teachers’ performance and work conditions are influenced by those actors’ action, who move themselves and modify their environment; e) in DE, the teaching work is defined by the use of technology, almost always reduced to the use of the computer, without understanding technology as an instrument that organizes the social relations established and without recognizing the individual as integral part of technology